Air Pollution and Time Use: Evidence from India - Jafar Jafarov; Tejendra P. Singh; Soham Sahoo (Institute of Labor Economics (IZA), 2023)
We investigate how air pollution impacts outdoor activity avoidance, leveraging changes in local wind direction in an instrumental variable setup for causal identification. Our findings reveal a substantial reduction in time spent outdoors during polluted days, mainly driven by decreased engagement in employment-related activities. This effect varies significantly across age, education level, usual principal activity status, consumption expenditure, and residential location. Moreover, reduced outdoor time due to air pollution can potentially promote a more equitable allocation of unpaid caregiving responsibilities within households via increased male involvement. Our results rule out information provision as the primary mechanism and remain robust under various sensitivity tests.
Keywords: D13; J22; O13; O17; Q53; Q56; 330; air pollution; time-use; labor supply; intrahousehold bargaining; avoidance behavior; India